Rating the Credit Raters - A. Seetharaman; Nitin Patwa; Shriram Nagarajan (STIE Malangkucecwara, 2019)
The current research identifies the rating of credit raters by evaluating how credit rating agencies are involved in rating the corporate. It determines the credibility and reliability of their scores based on various variables presenting the credit history and credit worthiness of corporate operating in global perspectives including the United States, UK and India. The paper indicates that there should be some agencies or financial bodies that oversee the processes and procedures of credit raters rating the corporate worldwide. The research explores and norms and practices of the rating of credit raters and determines how the selected variables would be helpful in determining the credibility and authenticity of the credit raters in financial markets. It highlights the implications of the opinions of these credit raters on the performance and future growth of the corporate and predicts what measures should be adopted in rating the credit worthiness of corporate operating in developing countries. This research indicates how these variables could affect the processes of credit raters and gives a direction to the policymakers and financial experts on the performance and creditworthiness of the financial opinions and ratings of the credit raters.